Antibodies against multiple post-translationally modified proteins aid in diagnosis of autoimmune hepatitis and associate with complete biochemical response to treatment - van den Beukel, Michelle D.; Stoelinga, Anna E. C.; van der Meer, Adriaan J.; van der Meulen, Stef; Zhang, Lu; Tushuizen, Maarten E.; van Hoek, Bart; Trouw, Leendert A. (Frontiers in Medicine, 2023)
Background (Auto)immune mediated and cholestatic liver disease (AILD) includes autoimmune hepatitis (AIH), primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC). Especially AIH is characterized by the presence of autoantibodies and elevated serum immunoglobulins. In rheumatoid arthritis, autoantibodies against post-translational modifications (PTMs) such as citrullination (Cit) and carbamylation (CarP) are used as diagnostic and prognostic markers, respectively. We studied the presence of six anti-PTM antibodies in patients with the three AILDs and non-AILD. Methods Antibodies against six PTMs (malondialdehyde–acetaldehyde adducts (MAA), advanced glycation end-products (AGE), CarP, acetylation (AL), Cit, and nitration (NT)) were tested in sera of patients with AILD (n = 106), non-AILD (n = 101) and compared with healthy controls (HC) (n = 100). Levels and positivity were correlated with clinical and biochemical features in a well-defined cohort of untreated AIH patients. Results Anti-PTM antibodies were more often detectable in sera from AILD patients compared with HCs (anti-MAA: 67.9% vs. 2.0%, anti-AGE: 36.8% vs. 4.0%, anti-CarP: 47.2% vs. 5.0% and anti-AL: 18.9% vs. 5.0%). In untreated AIH, time to complete biochemical response (CBR) was associated with anti-MAA, anti-AGE, anti-CarP and anti-AL antibodies. Significantly more patients with at least three anti-PTM antibodies attained CBR at 12 months of treatment (13 vs. 3 p = 0.01). Conclusion Anti-PTM antibodies are frequently present in AILD. The presence of anti-MAA, anti-AGE and anti-CarP antibodies correlates with the presence of AIH within this cohort. In AIH, harboring at least three anti-PTM antibody responses is positively associated with CBR. Determination of anti-PTM antibodies in liver disease may have diagnostic and prognostic value.